2013
DOI: 10.3892/ijo.2013.2223
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-resistant prostate cancer model: Differences in antioxidant system, apoptosis and cell cycle

Abstract: Differences in the antioxidant system, apoptotic mechanism and in cell cycle between prostatic cell lines could partially elucidate the development of cisplatin resistance. The aim of this study was to identify the most characteristic parameter for a particular cell line and/or a particular cisplatin treatment using a general regression model and to assess whether it is possible to use measured parameters as markers of cisplatin resistance. This study integrates the results of viability, antioxidant, flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…A decrease of the content of antioxidant enzymes in cancer cells reduces the efficacy of chemotherapy with carboplatin/paclitaxel (50). A relationship was observed between the degree of resistance to cytotoxic drug and the oxidative system in a cisplatin-resistant prostate cancer model (51). All these studies show the importance of investigating oxidative stress in patients with cancer.…”
Section: Evolution Of the Tumor Mass As Evaluated By 2d Bioluminescenmentioning
confidence: 67%
“…A decrease of the content of antioxidant enzymes in cancer cells reduces the efficacy of chemotherapy with carboplatin/paclitaxel (50). A relationship was observed between the degree of resistance to cytotoxic drug and the oxidative system in a cisplatin-resistant prostate cancer model (51). All these studies show the importance of investigating oxidative stress in patients with cancer.…”
Section: Evolution Of the Tumor Mass As Evaluated By 2d Bioluminescenmentioning
confidence: 67%
“…This resistance is further reflected in the lack of stimulation of the proportion of HaCaT cells in the subG1 fraction by cisplatin (Tables 2 and 3). This is likely due to the mutation in both alleles of p53 in HaCaT cells [104, 105], since it has been shown that cells with p53 mutation or p53 silencing are resistant to cisplatin-induced apoptosis [106, 107]. Cell cycle distribution analysis showed that 24 h pretreatment of HaCaT keratinocytes with 100 nM 1,25(OH) 2 D 3 or calcipotriol resulted in an increase in the proportion of cells in the G2/M phase of the cell cycle following incubation with 120 μM cisplatin for 24 h (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…as observed in patients with colorectal, lung and prostate cancer) [12], [13], [14] or acquired following cisplatin chemotherapy (as often seen in patients with ovarian cancer) [15]. The mechanisms of cisplatin resistance had been studied in several types of cisplatin resistant cell lines and appear to be multifactorial.…”
Section: Introductionmentioning
confidence: 99%